How Do Households Adjust to Trade Liberalization? Evidence from China's WTO Accession - Mi Dai; Wei Huang; Yifan Zhang (Institute of Labor Economics (IZA), 2018)
We investigate the impacts of trade liberalization on household behaviors and outcomes in urban China, exploiting regional variation in the exposure to tariff cuts resulting from WTO entry. Regions that initially specialized in industries facing larger tariff cuts experienced relative declines in wages. Households responded to this income shock in several ways. First, household members worked more, especially in the non-tradable sector. Second, more young adults co-resided with their parents, and thus household size increased. Third, households saved less. These behaviors significantly buffered the negative wage shock induced by trade liberalization.
Keywords: F14; F16; J20; R23; 330; household adjustments; trade liberalization; WTO